DIGITAL STORYTELLING IN ISLAMIC-BASED CONTENT AS A MEDIA TO PROMOTE ENGLISH AS FOREIGN LANGUAGE TO YOUNG ISLAMIC LEARNERS - Rizky Vita Losi; Virdyra Tasril; Rika Widya (Proceeding International Seminar of Islamic Studies, 2022)
The purpose of this study was to investigate the effect of digital storytelling by using Islamic stories (such as: Ibrahim and the fire, Leyla the sparrow, Alqaswa, etc) in promoting English to young Islamic learners. Since storytelling is a popular local wisdom in Indonesia and now, it develops to another form which is digital storytelling. There were 13 teachers participated in this study at Al-Washliyah Kindergarten, Klambir V Kebun. The data were collected from the questionnaire that was given to the teachers and then were analyzed by using SPSS 22.0. The result of this study indicated that there was a significant effect of storytelling by using digital stories in Islamic-based content to promote English to young Islamic learners (TScore was higher than TTable = 8,535 2,179).Keywords: Digital Storytelling, Islamic-based Content